Force concept inventory (FCI) representation of high school students (SMA & MA) - Jeffry Handhika; Farida Huriawati; Nur Fitriani (Journal of Physics: Theories and Applications, 2017)
There have been profiling the level of understanding of physics concept (dynamics and kinematics) of students' (SMA and MA) in madiun region. Profiling is done by using the Force Concept Inventory test. Samples were taken from 120 students from SMA and MA  in Madiun and Ponorogo. The results indicate that FCI test number 23 and number 16 is the most answered incorrectly by the students. Problem number 23 related to kinematics and test number 16 on Newton's third law. Only 24.16% of students answered correctly test numbers 23 and 25% of students answered correctly test number 16. Students SMA and MA do not understand the concept well and can’t represent concept in another shapes. These results provide an indication that the learning concept needs to be implementation at SMA and MA.